The relationship of dividend payout ratio with profitability ratios of the trading companies / Nurul Aida Mat Azam - Mat Azam, Nurul Aida (2012)
Under the uncertainty of economic market, trading company in Malaysia facing uncertainty and unpredictable risk that would affect their financial performance. Dividend payout ratio is too measured the percentage of earnings pay to shareholders. Sometimes the companies get many profits and do not pay or pay little amount of dividends to shareholders because they use the profit for retained earnings rather than pay dividend to shareholders and it can be worst if the profitability ratio of the company become worst in some situation. This study will assist in answering the question as well as identifying the relationship between the key variables and dividend payout ratio.The objectives of this research are to determine the independent variables that could affect the dependent variable, to find out the relationship between the dividend payout ratio as a dependent variable and operating profit margin,, return on equity and return on investment as an independent variables and to determine which factor that could gives the most impact on dividend payout. For this study, Multiple Regression Analysis will be used since there is more than one independent variable. Statistical Package for the Social Sciences (SPSS) was used in analyzing and processing the data. From result and findings it shown operating profit margin and dividend payout ratio is a determinant of dividend payout in trading companies because it have positive relationship, their beta always the highest and relationship of t-statistic is significant among other companies. So, as a conclusion it can be said that the level of profitability of the company effect the companies to pay dividend to their shareholders.